Exploring how education and sport are brought together in two different dual career programs for Danish soccer players: effects for the player`s current and future life - Olesen, J. S.; Gregersen, M. T. (Soccer & Society, 2023)
The article investigates dual-career (DC) programmes for young soccer players in Denmark. In these programmes, students pursue interests in both education and elite sport with the goal of becoming a better-rounded or `whole sports person`. Rather than critique this approach as incoherent, we employ Deleuze and Guattari`s concept of assemblage to explore how sport and education are brought together and the resulting ecologies for young people`s lives, present and future. We base our analysis on ethnographic studies of two DC programmes. We find that student-athletes enact the idea of the whole (sports)person in two quite different ways that either enhance or disrupt their agency to enact potential futures. We recommend greater awareness of how specific DC programmes create and deprive student-athletes of life opportunities.